2022
DOI: 10.55519/jamc-01-8695
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Initial Presentation of Primary Antiphospholipid Syndrome as Postpartum Symmetrical Peripheral Gangrene

Abstract: Antiphospholipid syndrome (APS) is an acquired prothrombic state with recurring thromboembolic and obstetric complications in the presence of antiphospholipid antibodies. Isolated skin manifestation especially symmetrical peripheral gangrene (SPG) in postpartum phase is reported rarely. To highlight this unusual presentation of APS with SPG we present a case of young female who developed SPG on her third postpartum day. Postpartum period runs a high risk of sepsis but development of such extensive and rapid is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…A French study of Mansour et al ( 25 ) reported of 14 recurrences following NA and 4% recurrence rate following ID in their study cohort. Khan et al ( 26 ) reported of 60 patients with a successful PTA drainage. Nevertheless, all recommendations are based on retrospective study data and small study cohorts ( 23 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A French study of Mansour et al ( 25 ) reported of 14 recurrences following NA and 4% recurrence rate following ID in their study cohort. Khan et al ( 26 ) reported of 60 patients with a successful PTA drainage. Nevertheless, all recommendations are based on retrospective study data and small study cohorts ( 23 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…as symmetrical peripheral gangrene. 3,4 Symmetrical peripheral gangrene can be an initial presentation of APS syndrome 5 or can present in the later course of the disease. 3 APS syndrome should be suspected and investigated in young patients presenting with symmetrical peripheral gangrene.…”
Section: Antiphospholipid Antibody (Aps) Syndrome Can Rarely Presentmentioning
confidence: 99%
“…Die bevorzugte chirurgische Behandlung hängt von den Patienten, der Compliance und der Erfahrung des konsultierten Arztes ab. Auch in der Literatur zeigten mehrere Studien gute Wirksamkeitsraten mittels Spaltung im Vergleich zur Tonsillektomie [ 11 , 14 , 25 ].…”
Section: Diskussionunclassified
“…Die Peritonsillitis bezeichnet die Ausbreitung auf das Peritonsillargewebe ohne Eiterverhalt [ 3 , 16 ]. Typische Symptome des PTA sind Odyno‑/Dysphagie, kloßige Sprache, Kieferklemme und beginnende Dyspnoe [ 14 , 31 ]. Zumeist zeigt sich eine unilateral geschwollene Tonsille, eine Rötung und Schwellung des Weichgaumens, Asymmetrie des Oropharynx sowie ein Uvulaödem begleitet von Fieber und Abgeschlagenheit [ 3 , 16 ].…”
unclassified
See 1 more Smart Citation